The Role of Brand Love in the Influence of Online Shopping Website Quality and Brand Experience on Costumer Loyalty - Sengguruh Nilowardono (International Journal of Social Science and Business, 2022)
Online shopping has become a way of life for many Indonesians nowadays. Quality online shopping websites do not automatically guarantee loyalty as well as brand experience. This can be seen from previous research, so this is a research gap that must be found a solution, therefore this research is needed to be able to help overcome this problem. This study aims to analyzed the effect of website quality and brand experience on brand loyalty with brand love as an intervening variable. The research method used purposive sampling technique where the data is examined using measurements by considering individual choices. The sample collection used a questionnaire, and the number of samples used is 100 respondents. The data analysis technique in this study uses Partial Least. Square (PLS). According to the findings of this study, both brand experience and brand love have a positive and substantial effect on consumer loyalty, whereas website quality has no positive and significant effect on brand loyalty. Brand love is a variable that influences consumer loyalty by mediating the impact of website quality and brand experience. The practical implication of this research is to provide insight that establishing consumer loyalty requires more than only relying on the quality of the website and brand experience, but also taking brand love into account.